MAKNA TIGA IKON GAJAH DI DALAM GEREJA SAINT PIERRE AULNAY PRANCIS - Panji Syofiadisna (Pusat Penelitian Arkeologi Nasional, 2020)
Abstract. Saint Pierre Aulnay Church is a Romanic-style church (Romanesque) that was built in the 12th century and is located in the Aquitaine Region, France. In this church, there are three elephant icons in the capital columns section. At the top of the icon, there is also an inscription in Roman that reads